The Role of Inclusive Psychological Teaching in College Volleyball Physical Education and Health - Chong Mu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
To obtain competitive advantage, there must be an increase in technology as well as public awareness of the brand. It is impossible to accomplish without a well-thought-out marketing plan, as well as awareness, execution, and organised advertising approaches. As a result, advertising is an important strategy for marketing items to customers. This study paper claims that it is important to look at the psychological appeal of food brands in relation to volleyball players, as well as customer behaviour while making product purchases. If a well-known celebrity appears in a commercial, people will be strongly affected by the brand or product. Psychological Attraction (PA) and Food Brand Advertisement (FBA) were independent variables in the research paradigm. Customer Behavior (CB) was employed as a Dependent Variable in this study. The information was gathered from 100 clients, though. SEM PLS 3 was used to analyse the obtained data. The findings revealed that while the association between PA and CB is minor, the relationship between FBA and CB is considerable.